Characterization of the major risk factors Cardiovascular diseases and analysis of hypertension as a complication among the relatively newly diagnosed patients all over Bangladesh: a reflective study - Shuvro, Asif Jahan (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.